Emotional Intelligence and Self-Adjustment in Grade 8 Students of Junior High School State 1 Baturetno - Muhammad Zulfa Alfaruqy (Jurnal Counseling Care, 2023)
Self-adjustment is needed for students, including at Sekolah Mengengah Pertama (SMP) Negeri 1 Baturetno, Wonogiri. Emotional intelligence is suspected to have a positive effect on students' self-adjustment. This research aimed to examine the relationship between emotional intelligence and adjustment and to review emotional intelligence and adjustment based on gender. This research tested three hypotheses. H1: There is a positive relationship between emotional intelligence and adjustment. H2: There are differences in emotional intelligence in terms of gender. H3: There are differences in adjustment in terms of gender. The total population was 256 students in grade 8. Based on the simple random sampling technique, 161 students were involved. The measurements used the Emotional Intelligence Scale (11 items, α = 0.860) and the Self-Adjustment Scale (14 items, α = 0.844). The results showed that there was a significant positive relationship between emotional intelligence and self-adjustment. Statistical analysis showed a correlation coefficient of 0.836 with a significance of 0.000 (p<0.05). Emotional intelligence makes an effective contribution of 68.8% to adjustment maturity. The study also found that in terms of gender, there were differences in emotional intelligence (male = 34.43, female = 36.68, p = 0.000) and differences in adjustment (male = 45.12, female = 47.75, p = 0.001). This research has implications for the urgency of optimizing emotional intelligence to cloud students' self-adjustment for schools and the state education department. Keywords: emotional intelligence; junior high school; self-adjustment; student